Chemical composition, rumen degradation, and gas production characteristics of some multipurpose fodder trees and shrubs during wet and dry seasons in the humid tropics - Larbi, Asamoah; Smith, Jimmy W.; Kurdi, I.O.; Adekunle, I.O.; Raji, A.M.; Ladipo, D.O. (Elsevier, 1998)
Seasonal variations in chemical composition, dry matter (DM) and nitrogen (N) degradation and gas production characteristics of 18 multipurpose trees and shrubs (MPTs) from the humid lowlands of West Africa were evaluated. The MPTs have potential for the development of integrated crop and livestock agroforestry technologies in the region. The experiment was conducted in Ibadan, southestern Nigeria during the main-wet (April-August) and dry (December-March) seasons. The MPTs were ranked by their degradation and gas production characteristics, and these were found to be related to chemical composition. There were wide variations among MPTs in crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF) and proanthocyaidin contents, DM and N degradation, and gas production characteristics. Dry matter degradation during the dry season ranged from 4126 to 868 g kg-1 and for N508 to 950 g kg-1. Crude protein, and rates of DM and N degradation were significantly correlated (r=0.48, P=0.037 for DM and r=0.56, P=0.032 for N). The rates and extents of DM and N degradation were significantly correlated with NDF and ADF during the wet season (r=-0.47 to-0.63). The volume of gas produced (r=-0.48 to -0.67) and initial gas production (r=-0.64 to -0.73) were highly correlated with the NDF and ADF in both seasons. The rate of DM degradation was significantly correlated with gas production variables in the minor-wet season. Ranking of the MPTs based on extent of DM and N degradation, and volume of gas produced for the main-wet and dry seasons were highly correlated. Based on degradation and gas production characteristics in the main-wet and the dry seasons, F. exasperata, S. nodosa, S. siamea, S. spectabilis, G. sepium, L. leucocephala and L. diversifolia were superior in quality to M. thonningii, A. angustissima and pterocarpum.